Sample instructional materials in communication arts I (English) geared towards the development-oriented curriculum - Parcon, Helen Casuga 1949- (1976)
In line with the latest revision in secondary education program aimed at equipping the student with necessary skills for gainful employment at least at the end of his secondary education, this paper is an essay to present sample instructional materials in Communication Arts I (English) which is geared to the development-oriented curriculum. After a careful study of the BVE Course Guide for Teaching Communication Arts I (English), the Prototype Guide in Practical Arts, and the Department Order No. 40 s. 1975, the writer planned out this presentation of the English language not merely as rules but as sets of rules. She then identified the main task and the subtasks for the four sample lessons. With these tasks, the writer prepared the sample instructional materials for the teacher's guide.
Vita.
Thesis (M.A. Language Education)--University of the Philippines, Diliman.
Keywords: English language -- Study and teaching (Secondary) -- Philippines -- Marikina City; Curriculum planning -- Philippines -- Marikina City; Teaching -- Philippines -- Marikina City -- Aids and devices